Tunable Fano resonances of Lamb modes in a pillared metasurface. (28th September 2017) - Jin, Yabin; EI Boudouti, EI Houssaine; Pennec, Yan; Djafari-Rouhani, Bahram
Abstract: In this work, Fano resonance is studied in a pillared acoustic metasurface, which originates from the avoided crossing of strongly coupled individual monopolar modes of two dissimilar pillars in one unit cell. The Fano resonance manifests itself as an out-of-phase compressional (monopolar) vibrations of the two pillars coupled through the plate. The Fano asymmetric transmission profile can be analyzed through the interference between the incident wave and the scattered wave emitted by resonant pillars. The peak in the asymmetric transmission is always maintained either the coupling of the two pillars is strong or weak. It is further found that the Fano resonance can be tuned by varying different geometrical parameters, such as the height/diameter of the pillars, the distance between the two pillars, or introducing an inner hole into the pillars which can possibly be filled with a liquid.